Pengaruh Penggunaan Digital Payment terhadap Perilaku Konsumsi Islam Masyarakat Surabaya Pada Masa Pandemi Covid-19 - Puspitasari, Siska Dwi; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2021)
During the Covid-19 pandemic, people's habits changed slightly, namely that almost all activities were carried out online including school, work, and shopping. To meet their daily needs, people have switched to using e-commerce and payment systems using digital payments to avoid direct contact with money. This study was conducted to determine the effect of the use of digital payments on the Islamic consumption behavior of the people of Surabaya during the Covid-19 pandemic. In this study using quantitative methods with a Likert scale measuring instrument with data analysis techniques using simple linear regression using SPSS 25.0. The results in this study indicate that the use of digital payments has a positive and significant effect on Islamic consumption behavior.